SDG7 - ensure access to affordable, reliable, sustainable, and modern energy - Nhamo, Godwell; Nhemachena, Charles; Nhamo, Senia; Mjimba, Vuyo; Savić, Ivana (Concise guides to the United Nations Sustainable Development Goals., 2020)
SDG7 aims to 'ensure access to affordable, reliable, sustainable and modern energy for all.' Meeting the demands of the 2030 agenda will be a unique challenge. National priorities and policy action need to be strengthened in order to fulfil the ambitious energy targets which SDG7 envisions. This book examines SDG7 and its implications for how energy operates as a driver of change for jobs, security, climate change, food production and increasing incomes. It provides a succinct overview of how SDG7 visualizes a world in which energy is universally accessible, increasingly efficient and renewable in order to create sustainable, inclusive and resilient communities. The key challenges such as public and private investment, regulatory frameworks and evolving business models are also considered so that a path forward towards the achievement of the goal and the transformation of global energy systems might become clear. Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.